Persuasion, social influence, and compliance gaining - Gass, Robert H. (Allyn and Bacon, 1999)
Persuasion, Social Influence, and Compliance Gaining looks at persuasion from a broad-based perspective, encompassing the full scope of persuasion as it is found in everyday life. This text examines persuasion in a variety of contexts and settings, including advertising, small groups, and face-to-face encounters. The text places special emphasis on newer avenues for studying persuasion, such as deception/deception detection and compliance gaining/compliance resisting. No other text provides this kind of breadth and depth of coverage. Linked to empirical research, Persuasion, Social Influence, and Compliance Gaining takes students from persuasion theory to qualified conclusions regarding the operation of persuasion in real-world settings. Praised for its highly accessible writing style, this text involves students and provides them with information and examples with which they can easily identify